Modelling Identification of Factors Affecting the Development of Sports Entrepreneurship Opportunities in The Field of Sports Education and Research - Ari Tri Fitrianto; Aulia Putri Yuliasti; Andi Kasanrawali; Dessalegn Wase Mola; Parveen Kumar (Faculty of Sport and Health Sciences, 2025)
Entrepreneurship development is a priority across all sectors, including the field of sports. This study sought to construct a model and determine the key factors that drive the expansion of entrepreneurial opportunities within sports education and research. Employing an exploratory-consequential approach with applied and developmental aims, the study was conducted in two phases. The qualitative phase involved semi-structured interviews with ten experts comprising academics, entrepreneurs, and sports administrators selected through convenience sampling. The quantitative phase included 52 randomly selected participants from the same population. Data collection instruments consisted of semi-structured interviews and a custom-designed questionnaire utilizing a 5-point Likert scale. Data analysis was performed using partial least squares structural equation modeling via SmartPLS 4. Exploratory factor analysis identified 52 items distributed across eight constructs. All constructs demonstrated strong validity and reliability, with factor loadings and AVE values exceeding 0.70. The final structural model exhibited a good overall fit and confirmed a significant positive impact of all eight factors (P < 0.001). The findings underscore the critical role of these dimensions in advancing sports entrepreneurship and suggest that reinforcing them could enhance the entrepreneurial framework within the domain of sports education and research.